A Fluorogenic AggTag Method Based on Halo‐ and SNAP‐Tags to Simultaneously Detect Aggregation of Two Proteins in Live Cells. (12th March 2019) - Jung, Kwan Ho; Kim, Sojung F.; Liu, Yu; Zhang, Xin
Abstract: Protein aggregation involves the assembly of partially misfolded proteins into oligomeric and higher‐order structures that have been associated with several neurodegenerative diseases. However, numerous questions relating to protein aggregation remain unanswered due to the lack of available tools for visualization of these species in living cells. We recently developed a fluorogenic method named aggregation tag (AggTag), and presented the AggTag probeP1, based on a Halo‐tag ligand, to report on the aggregation of a protein of interest (POI) in live cells. However, the Halo‐tag‐based AggTag method only detects the aggregation of one specific POI at a time. In this study, we have expanded the AggTag method by using SNAP‐tag technology to enable fluorogenic and biorthogonal detection of the aggregation of two different POIs simultaneously in live cells. A new AggTag probe—P2, based on a SNAP‐tag ligand bearing a green solvatochromic fluorophore—was synthesized for this purpose. Using confocal imaging and chemical crosslinking experiments, we confirmed thatP2 can also report both on soluble oligomers and on insoluble aggregates of a POI fused with SNAP‐tag in live cells. Ultimately, we showed that the orthogonal fluorescence ofP1 andP2 allows for simultaneous visualization of two different pathogenic protein aggregates in the same cell. Abstract : Two birds with a double stone : An effective method to simultaneously detect the aggregation of two proteins in live cells is provided. A Halo‐tag probe based on a molecular rotor in conjunction with a SNAP‐tag probe based on a solvatochromic fluorophore can detect two different protein aggregates in live cells through orthogonal fluorogenic responses with different color emissions.